Structure-fracture properties relationship for Polypropylene reinforced with fly ash with and without maleic anhydride functionalized isotactic Polypropylene as coupling agent - Igarza, Esteban (2013)
The deformation and fracture behavior of PP/ash composites with and without maleic anhydride functionalized iPP (MAPP) as coupling agent was investigated, focusing on the effect of ash content and loading conditions. A decreasing trend of tensile strength and strain at break values with filler content was observed for unmodified composites, whereas these properties were roughly independent of ash content for the composites with MAPP. In quasi-static fracture tests, all materials displayed ductile behavior. Most composites exhibited improved fracture properties with respect to the matrix as a result of the toughening mechanisms induced by the ash particles. Under impact loading conditions, in contrast, all materials displayed fully brittle behavior. Impact critical fracture energy values of the composites were higher than those of PP and they also presented a maximum which was explained in terms of the comprehensive analysis of the crystallinity development in PP. The incorporation of MAPP led to better dispersion of ash particles in the matrix but was detrimental to the material fracture behavior independently of loading conditions. Increased interfacial adhesion promoted by MAPP hindered particle-induced toughening mechanisms.